The Effects of the COVID-19 Outbreak on Selective Exposure: Evidence from 17 Countries. (3rd September 2022) - Zoizner, Alon; Sheafer, Tamir; Castro, Laia; Aalberg, Toril; Cardenal, Ana S.; Corbu, Nicoleta; de Vreese, Claes; Esser, Frank; Hopmann, David Nicolas; Koc-Michalska, Karolina; Matthes, Jörg; Schemer, Christian; et al.
ABSTRACT: A widely believed claim is that citizens tend to selectively expose themselves to like-minded information. However, when individuals find the information useful, they are more likely to consume cross-cutting sources. While crises such as terror attacks and pandemics can enhance the utility of cross-cutting information, empirical evidence on the role of real-world external threats in selective exposure is scarce. This paper examines the COVID-19 pandemic as a case study to test the extent to which citizens were exposed to information from cross-cutting sources on traditional and social media after the outbreak. Utilizing a two-wave panel survey among 14, 218 participants across 17 countries – conducted before and after the initial outbreak – we show that citizens concerned about COVID-19 were more exposed to cross-cutting information on traditional and social media. The positive relationship with cross-cutting exposure to traditional news was stronger in countries where governments adopted less stringent policy responses, and in countries with greater pandemic severity and weaker democratic institutions. Our comparative approach thus sheds light on the social and political contexts in which cross-cutting exposure can occur.